PERAN KOMUNIKASI PERSUASIF HUMAN RESOURCES DEVELOPMENT HOTEL BEST WESTERN PREMIER SOLO BARU DALAM MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA - Nurnawati Hindra H, Astried Eka Christiani, Dian Esti Nurati & (Transformasi, 2018)
The hotel is one of the role holders in the tourism industry because the hotel provides accommodation and service facilities. Good service can be seen from the quality of human resources in it. With competition in the world of hospitality that is getting tougher every hotel is competing to provide the best service for its guests. HRD (Human Resources Development) plays an important role in improving the quality of human resources because HRD has tasks that are directly related to employees. From this phenomenon, the authors are interested in examining the Role of Persuasive Communication in Human Resources Development in Improving the Quality of Human Resources. The theory used is the persuasive communication theory of Wilbur Schramm by using persuasive communication phases namely AIDDA (attention, Interest, Desire, Decision, Action) by arousing attention (attention) followed by developing interest (interest) so that the desire arises the coming of a decision (decision), namely the decision to take action (action). The type of research used in this study is descriptive research with qualitative methods. The results of the study explained that persuasive communication conducted by HRD Best Western Premier Hotel Solo Baru is by arousing concern among employees through messages by building communication by adjusting the situation, not always formal but with communication that can be received by employees, then to arouse the attention of HRD employees to conduct Best Employee and Best Attendance, there arises the interest of employees with enthusiasm, then the desire of employees to improve the quality of their performance by making decisions that are responsible for the work and the company, then the last action taken by employees is by improving and maximizing its performance. This has an impact on improving the quality of human resources.Keywords: persuasive communication, HRD, quality of human resources